Kształtowanie się tożsamości wielopoziomowej w państwach Europy Środkowej i Wschodniej po 1989 roku — zagadnienia teoretyczne - Węgrzyn-Odzioba, Liliana (Studia Etnologiczne i Antropologiczne, 2014)
Transformation of the socio-cultural realm in Central and Eastern Europe countries associated with the processes of globalization, as well as European integration, led to revitalize the debate on the dynamics and directions of changes of identity. Besides the categories associated with, so-called, “postmodern identity”, often questioning the very existence of dentity as such, other issues have appeared which indicate multilevel identity, taking into account relationship between European, national and regional identity. On the margin of this debate another and new subplot emerged, which is related to migration from non-European cultures and the possibility of spreading and therefore shaping a new model of European identity.